Status of Oxidants and Antioxidants in Pulmonary Tuberculosis with Varying Bacillary Load - Kumar3, Kanchan Mohod1, Archana Dhok2; Satish (Journal of Experimental Sciences, 2011)
When ROS production exceeds the detoxification capacity of systemic endogenic antioxidant defense, oxidative stress occurs. Severe oxidative stress has been reported in tuberculosis patients because of malnutrition and poor immunity. However, our knowledge of the antioxidant profile and its relation to lipid peroxidation in tuberculosis is very limited. We analyzed total hundred fresh untreated pulmonary tuberculosis samples with varying bacillary load and controls for oxidative stress markers viz; Malondialdehyde (MDA), Nitric oxide (NO) and Antioxidants viz; Superoxide Dismutase (SOD), Reduced Glutathione (GSH) and Vitamin C by calorimetric methods. The MDA &NO levels were high in AFB+,higher in AFB ++ and with AFB+++ had the highest levels while SOD,GSH &VITC levels were low in AFB+,lower in AFB++ and AFB+++ had the lowest levels. Our findings provide the evidence of enhanced free radical mediated process corresponded with more advanced disease. It might play a role in the pathology associated with tuberculosis. Hence, it appears that suitable antioxidant supplementations are required to protect them from free radical attack.